The impact of patient centered communication in managing Gardner′s syndrome - Gayathri Subramanian (Journal of Orofacial Sciences, 2015)
Effective patient communication and comprehension are fundamental toward empowering the patient to make optimal health decisions. Barriers in patient health literacy extend beyond cultural and language differences and can significantly impede this process. This case report illustrates a major communication gap that resulted in contradictory perceptions between a treating oncologist and a patient. The patient′s dentist was able to resolve this miscommunication and facilitate the patient′s acceptance of the recommended intravenous chemotherapy for management of malignant desmoid tumors occurring secondary to Gardner′s syndrome (GS). This report also documents classic craniofacial manifestations of GS including multiple unerupted supernumerary teeth, compound odontomas associated with a dentigerous cyst, as well as multiple osteomas in both arches and in the ethmoid and irregularly shaped radioopacities in both arches. In summary, effective patient-centered communication is a prerequisite for the optimal delivery of healthcare. Both interdisciplinary care and one-on-one patient-provider relationship center on coherent bidirectional communication.